The Impact of Incentives on the Performance of Office Staff at Barangay 178 Camarin Caloocan City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The objective of this study was to identify the Impact of incentives on the performance of officestaff in Barangay 178 Camarin CALOOCAN City. Specifically, the study aimed at identifyingthe demographic profile of the respondents, determining the incentives given to the officestaff, how incentives affect the performance of office staff in any different factors also, theproblems encountered on the performance of staff, and the recommended proposal ofimproving the incentives program to motivate the office staffs.In terms of Educational degrees, 47% of the respondents are undergraduates. Out of 44respondents, 22 or 50% have served two years in Barangay as office Staff. The majority of therespondents' salaries earned between 6,000 and 8,000. The data analysis proved that there isa significant between rewards, recognition, and appreciation as incentives affect productivity,leadership, satisfaction, loyalty, and teamwork. The results revealed it has a strong agreementthat can help to support the performance of office staff and also motivate them.This research study hopes to determine whether most employees are motivated by non-monetary incentives and are encouraged and motivated towards greater work performance.Overall, the researchers recommend strengthening the incentives program by giving officestaff health insurance in addition to gifts and other incentives so that office staff are not onlymotivated but also have access to necessary support to avoid illness and enjoy good health.
Keywords: Organizational Management